The Effect of Work Discipline, Leadership Style, and Training on the Performance of the Class IV Port Office and Port Authority (KSOP) Probolinggo City - Erni Rachmawati; Pompong Setiadi (DINASTI RESEARCH, 2022)
Human Resources (HR) is a very valuable asset or large investment that will become the main determinant of an organization or business. The right Human Resource Management (HR) for an organization or company will be a key factor and achieve maximum success. Excellent companies have strong human resources who can compete in the world and bring more success to the company. To increase the output to be achieved in a company, in this case the Probolinggo Port Authority and Harbormaster Office, it is necessary to pay attention to the discipline of its employees. Such as making KIP so that all employees can complete their tasks on time and according to what the company wants. The Probolinggo Port Authority and Harbormaster Office need to increase the knowledge of its employees to increase knowledge and experience in the work that the employee does. It is necessary to have regular training in 1 month in order to get maximum results. The Probolinggo Port Authority and Harbormaster Office need to create strict regulations, so that employees can obey the rules and not be careless in doing a job. And if the employee commits a violation, then there are consequences that must be accepted by the perpetrator to make the perpetrator more deterrent and more thorough and disciplined in his work.